Climate change policy in the European Union : confronting the dilemmas of mitigation and adaptation? - Jordan, Andrew, 1968- (Cambridge University Press, 2010)
The European Union (EU) has emerged as a leading governing body in the international struggle to govern climate change. The transformation that has occurred in its policies and institutions has profoundly affected climate change politics at the international level and within its 27 Member States. But how has this been achieved when the EU comprises so many levels of governance, when political leadership in Europe is so dispersed and the policy choices are especially difficult? Drawing on a variety of detailed case studies spanning the interlinked challenges of mitigation and adaptation, this volume offers an unrivalled account of how different actors wrestled with the complex governance dilemmas associated with climate policy making. Opening up the EU's inner workings to non-specialists, it provides a perspective on the way that the EU governs, as well as exploring its ability to maintain a leading position in international climate change politics.